Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12936-018-2171-2
|View full text |Cite
|
Sign up to set email alerts
|

Attractive toxic sugar baits for controlling mosquitoes: a qualitative study in Bagamoyo, Tanzania

Abstract: BackgroundMalaria elimination is unlikely to be achieved without the implementation of new vector control interventions capable of complementing insecticide-treated nets and indoor residual spraying. Attractive-toxic sugar baits (ATSBs) are considered a new vector control paradigm. They are technologically appropriate as they are simple and affordable to produce. ATSBs kill both female and male mosquitoes attracted to sugar feed on a sugary solution containing a mosquitocidal agent and may be used indoors or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 13 publications
(12 reference statements)
2
22
0
1
Order By: Relevance
“…aegypti, as the vector has an extremely limited flight range, often spending its entire life within a single household [5,35,40]. Other research with ATSBs has shown that endusers of these products prefer to have them placed indoors [14]. The successful design and placement strategy of DABS used in our experiments indicate that the device is ideal for in-home field testing.…”
Section: Discussionmentioning
confidence: 72%
“…aegypti, as the vector has an extremely limited flight range, often spending its entire life within a single household [5,35,40]. Other research with ATSBs has shown that endusers of these products prefer to have them placed indoors [14]. The successful design and placement strategy of DABS used in our experiments indicate that the device is ideal for in-home field testing.…”
Section: Discussionmentioning
confidence: 72%
“…This study was a proof of concept; it was a precursor to research and development into applicator design. Any ATSB design which has to be replenished regularly may increase costs and be vulnerable to user fatigue and compliance issues [23]. A sustainable ATSB design should identify a way to improve bait preservation and enhance the design to make it more acceptable to householders long-term.…”
Section: Discussionmentioning
confidence: 99%
“…A participatory formative approach such as Trials of Improved Practices (TIPs) could be used to assess community needs and preferences of new products, such as spatial repellents, on a small scale before introducing them more broadly [52]. Other important factors, not considered in this study, such as perception of harmful effects [53], willingness to pay [51] and introduction mechanisms, should also be explored in future studies assessing attitudes towards SR products.…”
Section: Discussionmentioning
confidence: 99%